Screening for hepatitis B virus infection among refugees diagnosed with latent tuberculosis in an Italian community - Tocco-Tussardi, I.; Fila, A.; Tralli, V.; Bordin, P.; Gazzani, D.; Majori, S.; Postiglione, C.; Tardivo, S.; Moretti, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Refugees are a growing population in the EU-27 area with specific health needs that are to be addressed in the most rapid and effective way at their arrival in the host country. Screening for Hepatitis B Virus infection is offered to specific categories and it could be useful and effective to extend its indications. The aim of this study was to define the epidemiological profile regarding Hepatitis B Virus infection in refugees hosted in the Asylum Seekers Centers of Verona (Italy), diagnosed with latent tuberculosis infection and eligible for chemoprophylaxis. Methods. We conducted a retrospective study in 715 refugees diagnosed with latent tuberculosis infection from January 1st, 2015 to December 31st, 2017. Screening for Hepatitis B Virus infection was offered to latent tuberculosis infection patients who were due to commence treatment. Subjects were tested for Hepatitis B surface Antigen and Hepatitis B core antigen total antibodies. None of the screened patients reported previous vaccination for hepatitis B. Results. Among the 715 refugees diagnosed with latent tuberculosis infection, 593 were eligible for treatment for latent tuberculosis infection. Of these, 211 (35.6%) accepted to be screened for Hepatitis B Virus infection. One hundred and ninety-five of the 211 (92.4%) came from African countries, and 16 (7.6%) from Asia; the majority (80.9%) were males. Median age was 23 years (95% CI 22-24). Of the 211, 58 individuals (27.5%) were Hepatitis B surface Antigen and Hepatitis B core antigen total antibodies positive; 74 (35.1%) were Hepatitis B surface Antigen negative and Hepatitis B core antigen total antibodies positive; and 79 (37.4%) were Hepatitis B surface Antigen and Hepatitis B core antigen total antibodies negative. Male gender and African origin were associated with a lower probability of being Hepatitis B surface Antigen- and Hepatitis B core antigen total antibodies-negative. Conclusions. Screening for Hepatitis B Virus is of paramount importance not only for the control and prevention of infection, but also in terms of long-term healthcare issues. Making screening more systematic can have an important impact on public health, while always considering cost-effectiveness and promotion of awareness among ethnic groups in order to gain their compliance to treatment/vaccination.